Merumuskan Kembali Pendidikan untuk Pembangunan Karakter Bangsa: Tantangan dan Arah Strategis - Hasanah, Siti; Islahudin, Islahudin; Jarwoto, Jarwoto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2024)
In the era of globalization, education plays a crucial role in shaping the character of a nation that is strong and has integrity. This article discusses the importance of reformulating the education system with a focus on building the nation's character. The aim is to face emerging challenges, such as the moral crisis, the negative influence of globalization, and significant social changes. Through a literature approach, this article explores the strategic directions that need to be taken in the process of reformulating character education, including the integration of moral and ethical values into the curriculum, the development of a positive school culture, and the increased participation of parents and communities in character education. This approach is expected to create an education system that not only produces intellectually intelligent individuals, but also those with strong character, responsibility, and the ability to contribute positively to nation building.